Mediating role of stock market volatility to evaluate asymmetries in the growth-degradation nexus in Nigeria - Abdullah AlGhazali; Nana Ize Musa; Saifullahi Sani Ibrahim; Ahmed Samour (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
This study explores the mediating role of stock market volatility in the economic growth and environmental degradation nexus in Nigeria using data covering period from 1984 until 2020. The study uses Nonlinear Autoregressive Distributed Lag (NARDL) and a nonparametric asymmetric causality model. While the Wald test in model 1 reveals evidence of weak long-run asymmetric nexus between CO2 and economic growth however, findings in model 2 indicates that stock market volatility (SMV) exerts a strong asymmetric effect in growth-CO2 relation in the long-run. The result of nonlinear model validates the inverted U-shaped growth-degradation nexus consistent with EKC hypothesis. The finding in model 1 reveals that investment exerts a strong impact on CO2 in both the short-run and long-run. On the other hand, the results in model 2 show that the positive component of economic growth has a positive and significant impact on CO2 in Nigeria. However, the negative component of economic growth has a negative impact on CO2. Moreover, the dynamic causality model reveals: (i) a feedback causality between CO2 and the negative component of GDP; and (ii) a unidirectional causality flowing from CO2 to the positive component of GDP. Similarly, result of nonlinear causality test reveals a feedback causality between CO2 and GDP. The implication of the finding suggests that while asymmetric properties of economic growth must be controlled in efforts of promoting environmental sustainability, the stock market has a dedicated role to play in widening access to funds for green investment in Nigeria and other developing economies.